Strategy of Housing and Settlement Area Services in Equality Development of Settlement Road Infrastructure in Batu City - Tri Maharani; Asep Nurjaman (Budapest International Research and Critics University, 2022)
Equitable quality infrastructure development is a driving factor and a challenge that must be implemented by the Department of Housing and Settlement Areas in terms of fulfilling urban or residential infrastructure needs and access to basic infrastructure such as residential environmental infrastructure. The purpose of this study was to analyze the efforts of the Department of Housing and Settlement Areas in equitable distribution of infrastructure development for access roads to settlements in Batu City. The type of research used was descriptive research with a qualitative approach. Data collection techniques through interviews, observation, and documentation. The subjects in this study consisted of the Head of the Infrastructure Section, and the Infrastructure Implementing Staff. The research was conducted at the Department of Housing and Settlement Areas of Batu City. Data analysis techniques used in this study consisted of data collection, data reduction, data presentation, and drawing conclusions. The results showed that the area in Batu City that had been paved was about 40% in Bumiaji District, 50% in Batu District and 70% in Junrejo District. In addition, the inhibiting factors for the development of paving road access infrastructure for settlements are often overlaps in handling development between the City government and the Village government and the role of the community is not yet optimal. Following up on the findings of this study, the equitable distribution of infrastructure development for residential road access should be optimized.